Morphological Productivity and Borrowing in Nigerian English: A Corpus-Based Study (Federal University Gusau Faculty of Education Journal, 2026)
Nigerian English (NigE) has developed into a unique variety of English, shaped by the interplay between speakers’ creative use of morphology and the influence of indigenous Nigerian languages. This study explores how NigE demonstrates morphological productivity and lexical borrowing, using a corpus-based approach to capture authentic language patterns. A carefully balanced corpus of 500,000 words was compiled from newspapers, online media, and recorded spoken interactions. Analyses focused on derivational processes, compounding, and the adaptation of loanwords, highlighting the strategies speakers employ to create new forms and meanings. The findings reveal that NigE exhibits robust morphological innovation, particularly in verb and noun formation, where affixation and compounding are frequently employed. Borrowed words, mainly sourced from Yoruba, Igbo, and Hausa, are often modified phonologically and morphologically to align with English norms, producing hybrid forms that enrich the NigE lexicon. This study underscores the dynamic relationship between English and indigenous languages in Nigeria, showing how speakers actively manipulate linguistic resources to meet social and communicative demands. The findings carry significant implications for sociolinguistic research, language teaching, and lexicography, advocating for recognition of NigE’s creative morphological processes in both academic study and pedagogical practice. By highlighting the innovative and adaptive nature of NigE, the study provides insights into how global English interacts with local linguistic ecologies.